Layered Green and Ampt Infiltration With Redistribution - Peter La Follette; Fred L. Ogden; Ahmad Jan (Water Resources Research, 2023)
Abstract Numerical solution of the one‐dimensional Richards equation (RE) accurately partitions precipitation into infiltration and runoff in capillary dominated soils. However, its application sometimes requires significant computational effort and presents reliability challenges. The Green and Ampt (G&A) approach represents a conservative and efficient method to calculate one‐dimensional infiltration but is limited to deep, well drained, uniform, non‐layered soils for a single rainfall event. The original G&A model and subsequent advancements represent wetting fronts as discrete objects, rather than discretizing the model domain in space, yielding a computationally simpler model than the RE. This paper describes an extension of the G&A method into layered soils on a continuous basis that we call Layered Green and Ampt with Redistribution (LGAR). Assumptions employed in the derivation include: uniform soil hydraulic properties within layers, single‐valued capillary head at the interface between soil layers, and no influence of groundwater table on soil moisture. Wetting fronts advance due to the combined effects of gravity and wetting front capillary drive in a layered soil profile. Results of multi‐month continuous LGAR simulations of infiltration using forcing and soil hydraulic data from USDA SCAN sites are compared against infiltration calculated using the HYDRUS‐1D RE solver using standard metrics. The assumptions employed in deriving the LGAR method limit its application to situations where cumulative potential evapotranspiration is greater than cumulative precipitation, typical of arid or semi‐arid conditions. LGAR is a mass‐conservative, computationally efficient, reliable and reasonably accurate method for simulating infiltration over extended time periods compared to the numerical solution of the RE in layered soils in arid and semi‐arid regions.